Innovation in primary education: final report, Project no. 8 of the CDCC - Council of Europe. Council for Cultural Co-operation. School Education Division (Strasbourg, France, School Education Division, Council for Cultural Co-operation, Council of Europe, 1988, 1988)
CDCC (88) 13 - DECS/EGT (87) 23 Chapter bibl.